Differences in In Vitro Disintegration Time among Canadian Brand and Generic Bisphosphonates - Wojciech P. Olszynski; Jonathan D. Adachi; K. Shawn Davison (Journal of Osteoporosis)
The objective of this study was to compare the disintegration times among Canadian-marketed brand (alendronate 70 mg, alendronate 70 mg plus vitamin D 5600 IU, and risedronate 35 mg) and generic (Novo-alendronate 70 mg and Apo-alendronate 70 mg) once-weekly dosed bisphosphonates. All disintegration tests were performed with a Vanderkamp Disintegration Tester. Disintegration was deemed to have occurred when no residue of the tablet, except fragments of insoluble coating or capsule shell, was visible. Eighteen to 20 samples were tested for each bisphosphonate group. The mean (±standard deviation) disintegration times were significantly P<0.05 faster for Apo-alendronate (26±5.6 seconds) and Novo-alendronate (13±1.1 seconds) as compared to brand alendronate (147±50.5 seconds), brand alendronate plus vitamin D (378±60.5 seconds), or brand risedronate (101±20.6 seconds). The significantly faster disintegration of the generic tablets as compared to the brand bisphosphonates may have concerning safety and effectiveness implications for patients administering these therapies.